Cresyl violet as a new contrast agent in probe‐based confocal laser endomicroscopy for in vivo diagnosis of gastric intestinal metaplasia - Sun, Yi‐Ning; Zhang, Ming‐Ming; Li, Li‐Xiang; Ji, Rui; Wang, Xiao; Li, Peng; Li, Yue‐Yue; Zheng, Meng‐Qi; Liu, Guan‐Qun; Zuo, Xiu‐Li; Li, Zhen; Li, Yan‐Qing (Journal of gastroenterology and hepatology, 2020)
Background and Aim Cresyl violet (CV) is a topical dye that allows simultaneous chromoendoscopy and in vivo confocal laser endomicroscopy in identification of neoplastic changes of the lower gastrointestinal tract without intravenous injection of fluorescein, but as yet no investigation has reported its application in the diagnosis of gastric intestinal metaplasia (GIM). This study aims to assess the feasibility as well as diagnosis accuracy of topical CV for in vivo diagnosis of GIM by using probe‐based confocal laser endomicroscopy (pCLE). Methods In this prospective, open‐label, feasibility study, 129 confocal videos from 22 patients with known GIM were analyzed and compared with corresponding histological images to establish the CV staining characteristics. In addition, 47 patients with known or suspected GIM were prospectively enrolled to evaluate the accuracy of this topical CV endomicroscopic imaging. Results Probe‐based confocal laser endomicroscopy with topical CV enabled clear visualization of the goblet cells, absorptive cells, and intestinal villi of GIM. The accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of pCLE diagnosis of GIM on a per‐location analysis was 93.01%, 91.95%, 93.51%, 86.96%, and 96.11%, respectively. The intraclass correlation coefficient for inter‐observer agreement and mean kappa value for intra‐observer agreement for the diagnosis of GIM was 0.82 and 0.87, respectively. Conclusions Topical CV enables real‐time chromoendoscopy in conjunction with pCLE examination of the stomach and warrants accurate diagnosis of GIM. It may be an acceptable and potentially alternative dye for confocal imaging in the future.